FOSTERING ENTREPRENEURIAL INTENTIONS AMONG STUDENTS - Mokosandib, Gabriela Ribka; Nuringsih, Kartika (International Journal of Application on Economics and Business, 2025)
The high unemployment rate in Indonesia is caused by rapid population growth, which causes an imbalance between the number of job seekers and the available jobs. One strategy that can be used to reduce unemployment is to exploit entrepreneurial potential. Therefore, researchers are interested in examining factors that might influence Tarumanagara University students' desire to become entrepreneurs. This research aims to determine the influence of self-efficacy, parents' socio-economic status, and entrepreneurship education on entrepreneurial intentions among undergraduate management students at Tarumanagara University. The theory of planned behavior serves as the theoretical foundation in conducting research. The research design used is quantitative with descriptive methods. The sampling technique used a purposive sampling technique. Data was collected using an online questionnaire with a sample size of 133 respondents. The data analysis technique used is Structural Equation Modeling. Data processing was carried out using SmartPLS software version 4.0. The results of this research show that self-efficacy does not have a positive and insignificant influence on entrepreneurial intentions, parents' socio-economic status has a positive and significant influence on entrepreneurial intentions, and entrepreneurship education has a positive and significant influence on entrepreneurial intentions. The results of this research can be a basis for educational institutions and the government to design programs that strengthen student self-efficacy, increase the accessibility of entrepreneurship education, and reduce socio-economic disparities.